Strategies to improve the therapeutic effect of pluripotent stem cell-derived cardiomyocytes on myocardial infarction - Xiao, Yang; Chen, Yihuan; Shao, Chunlai; Wang, Yaning; Hu, Shijun; Lei, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Myocardial infarction (MI) is a common cardiovascular disease caused by permanent loss of cardiomyocytes and the formation of scar tissue due to myocardial ischemia. Mammalian cardiomyocytes lose their ability to proliferate almost completely in adulthood and are unable to repair the damage caused by MI. Therefore, transplantation of exogenous cells into the injured area for treatment becomes a promising strategy. Pluripotent stem cells (PSCs) have the ability to proliferate and differentiate into various cellular populations indefinitely, and pluripotent stem cell-derived cardiomyocytes (PSC-CM) transplanted into areas of injury can compensate for part of the injuries and are considered to be one of the most promising sources for cell replacement therapy. However, the low transplantation rate and survival rate of currently transplanted PSC-CM limit their ability to treat MI. This article focuses on the strategies of current research for improving the therapeutic efficacy of PSC-CM, aiming to provide some inspiration and ideas for subsequent researchers to further enhance the transplantation rate and survival rate of PSC-CM and ultimately improve cardiac function.